Trend Sedimen Transport Pada Laut Ariake Utara, Japan - Jansen, Tommy (JURNAL ILMIAH MEDIA ENGINEERING, 2018)
The sediment balance is the balance of sediment volume entering and exiting a particular section of the coast or an estuary. These consists of the evaluation of sediment fluxes, sources and sinks from different processes that give rise to additions and subtractions within a control section of the coast in order to gain a better understanding of the coast system. The areas as a control volume are placed in north part and south part of the North Ariake Sea. Cross section AA, BB and cross section CC, DD are needed as the area that the flow through the control volume at spring tide and neap tide. The suspended sediment concentration entering and exiting within transport process at 30 August 2004 21:10:00 and 31 August 2004 15:46:40 of rectangular AABB and rectangular CCDD at spring and neap tide. The trend of transport sediment in rectangular AABB effected by tide it tends to catch little more sediment or deposition occurs. The trend of transport sediment in rectangular CCDD effected by tide it tends to export more sediment or erosion occurs. The phenomena in the north Ariake Sea that tidal flats keep existence and the concentration of sediment is higher around Chikugo River estuaries and nearshore, and the resuspension of sediment keep occurring at offshore of the north Ariake Sea. Keywords: sedimen transport, sedimen balance, coast, erosion, estuaries, resuspension